Amyotrophic Lateral Sclerosis Survival Score (ALS-SS): A simple scoring system for early prediction of patient survival. Issue 1 (17th February 2016) - Lunetta, Christian; Lizio, Andrea; Melazzini, Mario Giovanni; Maestri, Eleonora; Sansone, Valeria A.
Abstract: Our objectives were: (1) to identify independent prognostic factors to determine a survival score for amyotrophic lateral sclerosis (ALS) in a cohort of patients followed in the NEMO Centre (NEuroMuscular Omnicentre); (2) to replicate results in an independent cohort obtained from the Pooled Resource Open Access ALS Clinical Trial Consortium (PRO-ACT) database. Samples were collected from 428 ALS patients from the NEMO database and 2481 patients from the PRO-ACT database. Study design was a retrospective analysis with clinical and biochemical variables, using univariable and multivariable Cox models of analysis. Results showed that, in multivariable analysis, age at diagnosis, diagnostic delay, ALSFRS-R total score, Body Mass Index, aspartate aminotransferase and creatinine level were independently related to survival. These factors were recoded as categorical variables assigning a score from 5 to 15, and the sums of these scores were used to obtain the ALS-Survival Score (ALS-SS). This then allowed to identify three groups having different survival curves. The ALS-SS results were also replicated using data from the PRO-ACT database. In conclusion, considering independent prognostic factors, we were able to give an estimate of survival in our cohort of ALS patients. Whether this ALS-SS may be useful in clinical practice, and potentially in clinical trials, will have to be determined prospectively.